Hypo‐vascular hepatocellular carcinoma and liver transplantation: Morphological characteristics and implications on outcomes. Issue 7 (4th September 2019) - Aggarwal, Alok; Horwitz, Julian K.; Dolan, Dan; Kamath, Amita; Lewis, Sara; Facciuto, Matias; Grewal, Priya; Fiel, Maria Isabel; Schiano, Thomas; Facciuto, Marcelo E.
Abstract: Background: The clinical importance of hypovascular liver lesions in cirrhotic patients awaiting liver transplantation (LT) has not been fully investigated. The objective of this study was to characterize the clinicopathologic features and management of these tumors and to assess their impact on post‐LT outcomes. Methods: We performed a retrospective review of cirrhotic patients with lesions suspicious for hypovascular hepatocellular carcinoma (HCC) who underwent LT at a single institution from 2011‐ 2017. Results: We identified 22 pre‐LT patients with radiologic diagnosis of a lesion(s) suspicious for hypovascular HCC. There were 28 hypovascular lesions within the 22 patient cohort; 9 lesions (32%) converted to hypervascular HCC before LT and 19 lesions remained hypovascular at LT. 88% of hypovascular lesions were HCC on explant pathology. Compared to patients with hyper‐vascular HCC lesions, hypovascular HCC lesions underwent less preoperative tumor ablation (58% vs 89%; P < .01). Hypovascular HCC were more likely to be well‐differentiated (67% vs 11%; P < .01), but there were no differences in the microvascular invasion, tumor recurrence, or survival post‐LT. Conclusions: Hypovascular HCC has similar clinical outcomes and needs for transplantation as hypervascular HCC. The high prevalence of HCC within suspicious hypovascular lesions supports a similar monitoring and locoregional therapy strategy as for hypervascular HCC.